DBP Evaluations in DBPNet Sites: Is Race/Ethnicity a Significant Factor in Care?. Issue 1 (January 2020) - Augustyn, Marilyn; Silver, Ellen Johnson; Blum, Nathan; High, Pamela; Roizen, Nancy; Stein, Ruth E. K.
ABSTRACT: Objective: To examine whether there are differences between non-Hispanic white (NHW) and nonwhite (NW) children in referral questions, evaluations, and diagnoses during developmental behavioral pediatrician (DBP) evaluations at academic medical centers and the potential role of socioeconomic factors in any disparities noted. Design/Methods: This observational study used survey data from 56 DBPs at 12 sites participating in DBPNet. Child race and ethnicity were obtained from DBP report. Mixed-model logistic and linear regression analyses controlling for site, provider, and socioeconomic proxy variables (insurance type, parent education, and language spoken at home) were used to compare groups on referral concerns, evaluation procedures, and diagnoses. Results: Among the patients evaluated, 349 were NHW, 406 were NW (187 Hispanic, 135 black, 58 Asian/Pacific Islander, and 26 other/mixed), and 29 were missing race/ethnicity data. The mean waiting time controlling for site and provider was 20.4 weeks for NHW children and 20.5 weeks for NW children. Reasons for referral were similar in the NWH and NW groups, with only sleep problem concerns being more frequent among NHW children (9.2% vs 3.4% NW, p = 0.01). Patients also had similar evaluations in the 2 groups; the only differences found were that more NHW than NW children had genetic testing (33.1% vs 19.3%, p = 0.02), ophthalmology evaluations (8.7% vs 3.4%, p = 0.03), and psychopharmacologic evaluations (19.1% vs 9.7%, p = 0.008). Numbers and types of diagnoses did not vary by race/ethnicity. Conclusion: This study suggests little inequality between NHW and NW children in wait time to care, reasons for referral, workup, or final diagnosis for initial DBP evaluation at these 12 academic DBP centers when socioeconomic factors are considered. Nevertheless, because differences in these related factors may be mechanisms through which racial/ethnic disparities can arise, it will be important to consider them in planning models and care protocols for underserved communities.